A Genealogy of Antihero - Murat KADİROĞLU (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
“Antihero”, as a literary term, entered literature in the nineteenth century with Dostoevsky, and its usage flourished in the second half of the twentieth century. However, the antihero protagonists or characters have been on stage since the early Greek drama and their stories are often told in the works of the twentieth century literature. The notion of “hero” sets the base for “antihero”. In every century, there are heroes peculiar to their time; meanwhile, antiheroes continue to live as well, though not as abundant as heroes in number. The gap between them in terms of their personality, moral code and value judgements is very obvious in their early presentation; however, the closer we come to our age, the vaguer this difference becomes. In contemporary literature, antiheroes have begun to outnumber heroes as a result of historical, political and sociological facts such as wars, and literary pieces have tended to present themes of failure, inaction, uncertainty and despair rather than heroism and valour. This study argues that Second World War has the crucial impact on the development of the notion of modern antihero. As a consequence of the war, “hero” as the symbol of valour, adventure, change and action in the legends and epic poems has been transformed into “antihero” of failure and despair, especially in realist, absurdist and existentialist works written during/after the Second World War.